Hubungan Gerakan Literasi Sekolah Dengan Kemampuan Membaca Pemahaman Siswa Kelas Tinggi UPT SD Inpres 5/81 Ajangpulu Kecamatan Cina Kabupaten Bone - RAHMAH NITA RUKMINA SARI; Rukayah Rukayah; Mujahidah Mujahidah (Universtas Negeri Makassar, 2022)
This research is a quantitative research with a correlational approach which aims to: 1) describe the school literacy movement of High Grade Students of UPT SD Inpres 5/81 Ajangpulu, Cina District, Bone Regency, 2) describe the reading comprehension ability of High Grade Students of UPT SD Inpres 5/81 Ajangpulu China Subdistrict, Bone Regency, 3) describe the relationship between the school literacy movement and the reading comprehension ability of high grade students of UPT SD Inpres 5/81 Ajangpulu, Cina, Bone Regency, with a total of 32 students. Data collection was carried out using questionnaires and tests. Data analysis technique with descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, the results of the research on the school literacy movement have an average of 79.40 and a percentage of 79.40% with a good category and the average reading comprehension ability of high-class students has an average of 62.40 and a percentage of 62.40%. with medium category. Based on the results of inferential statistical analysis, the tcount value (2.81) is greater (>) the ttable value (1.6973) at a significance level of 21%. Thus H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between the School Literacy Movement and the Reading Comprehension Ability of High Grade Students of UPT SD Inpres 5/81 Ajangpulu, Cina District, Bone Regency. Penelitian ini adalah penelitian kuantitatif dengan jenis pendekatan korelasional yang bertujuan untuk: 1) mendeskripsikan gerakan literasi sekolah Siswa Kelas Tinggi UPT SD Inpres 5/81 Ajangpulu Kecamatan Cina Kabupaten Bone, 2) mendeskripsikan kemampuan membaca pemahaman Siswa Kelas Tinggi UPT SD Inpres 5/81 Ajangpulu Kecamatan Cina Kabupaten Bone, 3) mendeskripsikan gambaran hubungan gerakan literasi sekolah dengan kemampuan membaca pemahaman siswa kelas tinggi UPT SD Inpres 5/81 Ajangpulu Kecamatan Cina Kabupaten Bone dengan jumlah siswa 32 orang. Pengumpulan data dilakukan dengan menggunakan angket dan tes. Teknik analisis data dengan analisis statistik deskriptif dan analisis statistik inferensial. Berdasarkan hasil analisis statistik deskriptif diperoleh hasil penelitian gerakan literasi sekolah memiliki rata-rata 79,40 dan persentase 79,40% dengan kategori baik dan rata-rata kemampuan membaca pemahaman siswa kelas tinggi memiliki rata-rata 62,40 dan persentase 62,40% dengan kategori sedang. Berdasarkan hasil analisis statistik inferensial menunjukkan nilai thitung (2,81) lebih besar (>) nilai ttabel (1,6973) pada taraf signifikansi 5%. Dengan demikian H0 ditolak dan H1 diterima. Kesimpulan penelitian bahwa terdapat hubungan yang signifikan antara Gerakan Literasi Sekolah dengan Kemampuan Membaca Pemahaman Siswa Kelas Tinggi UPT SD Inpres 5/81 Ajangpulu Kecamatan Cina Kabupaten Bone.